Possibilities of collecting evidences about crime act of sexual exploitation in human beings - Mijalković Saša (Temida)
Collecting evidences about organized crime act of sexual exploitation in human begins often is very difficult because of high level of organization, secrecy ant precaution taken during committing prostitution, pornography, sex tourism and human trafficking. On the other side, high illegal profit enable criminals to engage "expensive" and experienced lawyers, whose often make values and reliability of collected evidences questionable, appealing to irregularities during police collecting procedure. Among traditional criminalities methods and proofing activities, in the study, modern tendencies in special investigative measures and techniques are considered. After that, there is pointing at specificity, meaning and value of material tracks and objects, which are essential for proofing crime act or perpetrator’s guiltiness. On the end, there is pointing at importance of victims’ cooperation in collecting evidences about their sexual exploitation.